Initiatives for Religious Moderation in West Sumatra: Preserving the Harmony of Tradition and Islam - D, Rusyaida; Fadlli Marh, Noor; Taufiq, M; Fadhli, M; Sabri (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2024)
Adat Basandi Syarak, Syarak Basandi Kitabullah (ABS-SBK) remains deeply embedded in the idealized worldview of Minangkabau society in West Sumatra, serving as a foundational philosophy that harmonizes tradition and Islam. However, contemporary religious dynamics demand adaptation, particularly concerning religious moderation, as West Sumatra is often perceived as deficient in this aspect due to its strong religious identity. This study explores the strengthening of religious moderation through strategic initiatives based on ABS-SBK in three regencies—Tanah Datar, Agam, and Lima Puluh Kota—culturally known as Luhak Nan Tigo, the historical heartland of the Minangkabau ethnic group. Qualitative interviews reveal that each luhak responds to the challenges of modernity through distinct approaches: Tanah Datar relies on traditional authorities and historical sites, Agam reinforces its identity as a Madani (civilized) district, while Lima Puluh Kota emphasizes managing social diversity. This study argues that the Minangkabau people ought to ideally achieve a higher religious harmony index than their current standing. It seeks to position these efforts within the ABS-SBK framework as local wisdom, the identity of Islam as a minority, and its relation to maqāṣid al-sharī‘ah.